Neues über die von Ionescu beschriebenen Proturen (Apterygota). - Tuxen, Sören Ludvig Paul (Contributions to Entomology = Beiträge zur Entomologie, 1961)
Among the 22 species and 5 varieties described by Ionescu the following 10 - perhaps 12 - species and none of the varieties are valid, but 2 as synonyms: Eosentomom forsslundi Ion. - as a synonym of E. germanicum Prell (Tuxen 1960a); Ionescuellum carpaticum Ion. (Tuxen 1960b). Syn.: I. helenicum Ion.; Acerentulus aureus Ion. (= macrocephalus Ion.) - as a synonym of A. confinis Berlese; Acerentulus muscorum Ion.; Acerentulus trägardhi Ion. (Syn.: insignis Conde; globocephalus Ion.); Acerentomon mesorhinus Ion.; Acerentomon quercinum Ion. (Syn.: quercinum var. simplex Ion.; intermedium Ion.); ? Acerentomon campestre Ion. (Syn.: campestre var. nemorale Ion.; romanicum Ion.) - but perhaps as a synonym of preceding species. Acerentomon gallicum Ion. (Syn.: gallicum var. elongatum Ion., maximum Ion., variatum Ion., variatum var. proximum Ion., variatum var. assimile Ion.).; ? Acerentomon hayei Ion. (Syn.: hyalinum Ion.) - but perhaps as a synonym of the preceding species; Acerentomon balcanicum Ion. (Syn.: barei Ion.).; Acerentomon rostratum Ion. Nomenclatural Acts balcanicum Ionescu, 1933 (Acerentomon), Lectotype barei Ionescu, 1933 (Acerentomon), Lectotype gallicum Ionescu, 1933 (Acerentomon), Lectotype hayei Ionescu, 1933 (Acerentomon), Lectotype mesorhinus Ionescu, 1930 (Acerentomon), Lectotype quercinum Ionescu, 1932 (Acerentomon), Lectotype variatum Ionescu, 1933 (Acerentomon), Lectotype aureus Ionescu, 1930 (Acerentulus), Lectotype macrocephalus Ionescu, 1933 (Acerentulus), Lectotype trägårdhi Ionescu, 1937 (Acerentulus), Lectotype carpaticum Ionescu, 1930 (Paraentomon), Lectotype